Assessing the Spiritual Needs and Practices of Oncology Patients in Turkey. Issue 2 (March 2015) - Dedeli, Ozden; Yildiz, Emel; Yuksel, Safak
Abstract : The purpose of this study was to assess the oncology patients' spiritual needs and activities. Besides, the study was to provide clinical evaluation of the feasibility and usefulness of the Patients Spiritual Needs Assessment Scale. This descriptive and cross-sectional study was performed by using a demographic and spiritual practices questionnaire, the Turkish version of the Patients Spiritual Needs Assessment Scale. The results of our study demonstrated that the most common spiritual needs of patients with cancer were "to address issues before death and dying" (100%), "feel a sense of peace and contentment" (94.8%), and "for companionship" (93.5%). Spiritually assessing a patient with cancer requires knowledge of how spiritual needs may manifest and how to talk with a client about his or her spiritual needs. These findings can help nurses to begin this process of providing spiritual care for patients with cancer.